Revestimentos comestíveis a base de quitosana e extrato de alecrim (rosmarinus officinalis l.) e sua aplicabilidade na carne bovina - Lima, Allison Ferreira de (2019)
The objective of the research was to elaborate and evaluate edible coatings based on chitosan and rosemary extract (Rosmarinus officinalis L.) and its applicability on beef. At the beginning, the preparation of rosemary extracts at concentrations of 4% and 8%, as well as preparation of the polymer mixture and consequent immersion of the meat in this content and in distilled water (control) for the physical analyzes (pH, (coliforms at 45 ° C and the shelf life of mesophiles, psychrotrophs, Staphylococcus ssp. and detection of Salmonella spp.) and antioxidant activity (TBARS). The mechanical properties, water vapor permeability (PVA), color, transparency, solubility and moisture absorption of the films were evaluated. The results of the physical analyzes show that there was a significant effect (p <0.05) between coatings types and shelf life for pH and all color parameters studied (L, a * and b *). The highest water retention capacity occurred at the concentration of 8% of the extract. Among the treatments on weight loss in cooking, these results relate to polymer blends. The shear force also showed a difference between the treatments and the times, all the samples had a decrease in the shear force over time. In the microbiological analyzes, the absence of Salmonella spp. in 25 g of sample. As for coliforms at 45º C, values of 1100 NMP / g were found both in the treated samples and in the control at time 0 (single evaluation day). The count of aerobic mesophilic microorganisms differed significantly (p <0.05) in the coatings where the rosemary extracts were included in the other treatments, showing a tendency to reduce these microorganisms, as well as in psychrotrophic microorganisms. It was observed immediate action of the coatings against the propagation of Staphylococcus spp., Where the samples did not present statistical difference (p> 0.05) between the treatments from day 2. The coatings where there was the inclusion of rosemary extracts, demonstrated significant antioxidant capacity between treatments and over the evaluation times. Concerning the films, thickness variation was observed, however, there was no significant difference (p> 0.05) between these values. As for solubility, there was no significant difference (p> 0.05) between treatments. The moisture absorption varied significantly (p <0.05) between the control treatment and those treated with the extracts. In the PVA evaluation, there was a significant difference (p <0.05) between the control treatments and with 8% of extract, 0.41 and 0.70 g.mm/h.m².kPa, respectively, avoiding the deterioration process in food. In relation to the mechanical tests, the control requires less tension than the samples with extracts, to undergo deformation, however, there is no statistical difference (p> 0.05). Regarding the force required to break the test specimen, it was observed that the control film is more resistant than films with extracts, presenting a statistical difference (p <0.05). Thus, it was concluded that the coatings based on chitosan and rosemary extract (Rosmarinus officinalis L.) had an influence on the conservation and quality of refrigerated beef, and the coating with the lowest extract concentration (4%) was the most indicated, because it has the lowest cost of production, keeping the meat as close to the natural one